Understanding Consumer Decisions: Factors Influencing Men's Choice of Premium Barbershops in Kediri City" - Gustiawan, Wahyu Dede; Sudarmiatin, Sudarmiatin; Rahayu, Wening Patmi (RISK : Jurnal Riset Bisnis dan Ekonomi, 2024)
The premium barbershop industry in Indonesia continues to grow in line with the increasing consumer awareness of the modern lifestyle that prioritizes quality and aesthetics. This study aims to analyze the factors that affect male consumers with middle to upper income in choosing premium barbershop services in Kediri City. The study uses a qualitative approach with an in-depth interview method with seven respondents who have a monthly income between Rp5 million to Rp7 million. The results show that consumer decisions are influenced by five main factors: service quality, venue atmosphere, price as a status symbol, and social validation through social media. Income and also lifestyle. Service quality, particularly reliability and empathy, plays a key role in building customer satisfaction. In addition, the atmosphere of the place is attractive and comfortable, as well as the perception of prices that reflect quality, encouraging consumers to choose premium services. Social media is also an important element in shaping positive consumer perceptions through visual content and customer reviews. The research's contributions include strengthening SERVQUAL's theory and customer experience in the context of local services, as well as providing practical recommendations for premium barbershop businesses to improve their services and marketing strategies. This research is expected to be the basis for further studies on consumer behavior in the premium service sector.